Fractional CO2 laser therapy: a new challenge for vulvovaginal atrophy in postmenopausal women. (4th July 2017) - Siliquini, G. P.; Tuninetti, V.; Bounous, V. E.; Bert, F.; Biglia, N.
Abstract: Objective: To evaluate the effects of CO2 laser in the treatment of vulvovaginal atrophy (VVA) in postmenopausal women. Methods: VVA was assessed in 87 postmenopausal women (mean age 58.6 ± 6.9 years) before and after the treatment. The protocol consisted of three monthly treatments and included the treatment of vulva. Subjective measures included VAS (Visual Analog Scale) both for vaginal dryness and dyspareunia; DIVA (Day-by-day Impact of Vaginal Aging); a questionnaire on treatment satisfaction and one about the degree of pain during the procedure. Objective measures included VHI (Vaginal Health Index) and VVHI (Vulvo-Vaginal Health Index). Time points of the study were at the screening visit (T0), at baseline (T1), at week 4 (T2), at week 8 (T3), after 3 months since the last laser application (T4), after 6 months (T5), after 9 months (T6), after 12 months (T7) and after 15 months (T8). Results: Treatment induced significant improvement in the VAS score. After treatment, VHI and VVHI indicated no VVA and this improvement was long lasting. Multivariate analysis showed that the time of follow-up was correlated with better VHI and VVHI ( p  < 0.001). DIVA improved over time ( p  < 0.001). Conclusions: This study shows that CO2 laser treatment induces a significant and long-lasting improvement of symptoms.